2023
DOI: 10.3389/fmicb.2023.1107976
|View full text |Cite
|
Sign up to set email alerts
|

Current evidence and clinical relevance of drug-microbiota interactions in inflammatory bowel disease

Abstract: BackgroundInflammatory bowel disease (IBD) is a chronic relapsing-remitting disease. An adverse immune reaction toward the intestinal microbiota is involved in the pathophysiology and microbial perturbations are associated with IBD in general and with flares specifically. Although medical drugs are the cornerstone of current treatment, responses vary widely between patients and drugs. The intestinal microbiota can metabolize medical drugs, which may influence IBD drug (non-)response and side effects. Conversel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 190 publications
0
5
0
Order By: Relevance
“…It has been reported that patients with UC have a different gut microbiota 27 and that steroid use may affect the gut microbiota in patients with inflammatory bowel disease. 28 An interaction between gut microbiota and the immune system has also been reported. 29,30 For example, maintaining remission after steroid administration may change the gut microbiota to a composition that is less likely to relapse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that patients with UC have a different gut microbiota 27 and that steroid use may affect the gut microbiota in patients with inflammatory bowel disease. 28 An interaction between gut microbiota and the immune system has also been reported. 29,30 For example, maintaining remission after steroid administration may change the gut microbiota to a composition that is less likely to relapse.…”
Section: Discussionmentioning
confidence: 99%
“…These factors may include gut microbiota and immune dysregulation. It has been reported that patients with UC have a different gut microbiota 27 and that steroid use may affect the gut microbiota in patients with inflammatory bowel disease 28 . An interaction between gut microbiota and the immune system has also been reported 29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…The digestive system is one of the most extensive areas of pharmacomicrobiomics because it is home to complicated and varied microbiota that is critical in drug metabolism and efficacy. 189 , 389 Gut microbiota has also been demonstrated to impact outcomes of drugs used to treat a variety of digestive diseases, e.g., inflammatory bowel diseases (IBD) and irritable bowel syndrome (IBS). 390 Patients with IBD have been detected to have altered gut microbiota composition and function, which may affect IVDR.…”
Section: Pharmacomicrobiomics Of Ivdr In Human Diseasesmentioning
confidence: 99%
“…Recently, the research of drug-microbiota interactions has become a systematically developed field, due to the increasing fascination with the variation of gut microbiota. 62,[186][187][188][189] This field has given rise to various sub-disciplines, including pharmacomicrobiomics, pharmacometabonomics, and pharmacometagenomics. 159,[190][191][192][193] These sub-disciplines aim to study the effect of microbiota on PK and PD, and to explore how microbiota variation affects IVDR in human diseases [194][195][196][197] (Fig.…”
Section: Emerging Of Pharmacomicrobiomics In Ivdrmentioning
confidence: 99%
“… 17 Colon-targeting of thiopurines may, therefore, be applied specifically in IBD to minimize the side effects of systemic thiopurine treatment, as previously proposed. 18 Colon-targeting per se has been achieved through the use of indigestible fibers (such as resistant-starch, pectin, chitosan, chondroitin, dextran, or guar gum) applied as coating materials that are degraded by gut bacteria. 19 …”
Section: Introductionmentioning
confidence: 99%